Application of GUSED‐VBS 2 Model for Flow and Sediment Transport in Vegetated Strips to Improve Water Quality†. (6th December 2017) - Akram, Sina; Yu, Bofu
Abstract: Vegetated buffer strips change flow hydrology and sediment transport by increasing resistance to the flow and intensifying infiltration. GUSED‐VBS 2 is a process‐based mathematical model developed to simulate flow characteristics and the fate and transport of sediment in the backwater region upstream of vegetated strips and within them. The model also predicts the concentration and delivery of different particle sizes leaving the vegetated strips and reaching open water bodies. GUSED‐VBS 2 assumes that entrainment and deposition processes occur simultaneously and uses the Green–Ampt approach to simulate infiltration and gradually varied flow and kinematic wave approximation to simulate the water profile in the backwater region and within the vegetated strip respectively. The modified GUEST model approach was used to model the fate and transport of sediment in vegetated strips. Field data were used to evaluate the model predictions of the efficiency of vegetated strips in reducing runoff, sediment concentration and sediment delivery, and the results showed that GUSED‐VBS 2 performed much better in controlled conditions compared to field conditions. The performance of the GUSED‐VBS 2 and WEPP models in simulating particle size distribution in the outflow was compared with different model evaluation criteria and GUSED‐VBS 2 showed better performance compared to WEPP. Copyright © 2017 John Wiley & Sons, Ltd.